Escherichia coli type-1 fimbriae are critical to overcome initial bottlenecks of infection upon low-dose inoculation in a porcine model of cystitis. Issue 10 (8th October 2021) - Stærk, Kristian; Grønnemose, Rasmus Birkholm; Nielsen, Thomas Kastberg; Petersen, Nicky Anúel; Palarasah, Yaseelan; Torres-Puig, Sergi; Møller-Jensen, Jakob; Kolmos, Hans Jørn; Lund, Lars; Andersen, Thomas Emil
Abstract : Most uropathogenic Escherichia coli (UPEC) express type-1 fimbriae (T1F), a key virulence factor for urinary tract infection (UTI) in mice. Evidence that conclusively associates this pilus with uropathogenesis in humans has, however, been difficult to obtain. We used an experimental porcine model of cystitis to assess the role of T1F in larger mammals more closely related to humans. Thirty-one pigs were infected with UPEC strain UTI89 or its T1F deficient mutant, UTI89Δ fimH, at inoculum titres of 10 2 to 10 8 colony forming units per millilitre. Urine and blood samples were collected and analysed 7 and 14 days post-inoculation, and whole bladders were removed at day 14 and analysed for uroepithelium-associated UPEC. All animals were consistently infected and reached high urine titres independent of inoculum titre. UTI89Δ fimH successfully colonized the bladders of 1/6 pigs compared to 6/6 for the wild-type strain. Intracellular UPEC were detectable in low numbers in whole bladder explants. In conclusion, low doses of UPEC are able to establish robust infections in pigs, similar to what is presumed in humans. T1F are critical for UPEC to surpass initial bottlenecks during infection but may be dispensable once infection is established. While supporting the conclusions from mice studies regarding a general importance of T1F in successfully infecting the host, the porcine UTI models' natural high, more human-like, susceptibility to infection, allowed us to demonstrate a pivotal role of T1F in initial establishment of infection upon a realistic low-inoculum introduction of UPEC in the bladder.